TGA Transcription Factors Activate the Salicylic Acid-Suppressible Branch of the Ethylene-Induced Defense Program by Regulating ORA59 Expression. Issue 4 (2nd July 2014) - Zander, Mark; Thurow, Corinna; Gatz, Christiane
Abstract : Two antagonistic hormonal pathways merge at the promoter of a crucial activator of one of the pathways. Abstract: Salicylic acid (SA ), a hormone essential for defense against biotrophic pathogens, triggers increased susceptibility of plants against necrotrophic attackers by suppressing the jasmonic acid-ethylene (ET ) defense response. Here, we show that this disease-promoting SA effect is abolished in plants lacking the three related TGACG sequence-specific binding proteins TGA2, TGA5, and TGA6 (class II TGAs). After treatment of plants with the ET precursor 1-aminocyclopropane-1-carboxylic acid (ACC ), activation of all those genes that are suppressed by SA depended on class II TGAs. Rather than TGA binding sites, GCC-box motifs were significantly enriched in the corresponding promoters. GCC-box motifs are recognized by members of the superfamily of APETALA2/ETHYLENE RESPONSE FACTORs (ERFs). Of 11 activating ACC -induced APETALA2/ERFs, only ORA59 (for OCTADECANOID-RESPONSIVE ARABIDOPSIS APETALA2/ETHYLENE RESPONSE FACTOR domain protein59 ) and ERF96 were strongly suppressed by SA . ORA59 is the master regulator of the jasmonic acid-ET -induced defense program. ORA59 transcript levels do not reach maximal levels in the tga2 tga5 tga6 triple mutant, and this residual activity cannot be suppressed by SA . The ORA59 promoter contains an essential TGA binding site and is a direct target of class II TGAs as revealed by chromatin immunoprecipitation experiments. We suggest that class II TGAs at the ORA59 promoter constitute an important regulatory hub for the activation and SA suppression of ACC -induced genes.